Psychometric properties of the Geriatric Anxiety Inventory (GAI) and its short-form (GAI-SF) in a clinical and non-clinical sample of older adults. (11th August 2014) - Johnco, Carly; Knight, Ashleigh; Tadic, Dusanka; Wuthrich, Viviana M.
ABSTRACT: Background: The Geriatric Anxiety Inventory is a 20-item geriatric-specific measure of anxiety severity. While studies suggest good internal consistency and convergent validity, divergent validity from measures of depression are weak. Clinical cutoffs have been developed that vary across studies due to the small clinical samples used. A six-item short form (GAI-SF) has been developed, and while this scale is promising, the research assessing the psychometrics of this scale is limited. Methods: This study examined the psychometric properties of GAI and GAI-SF in a large sample of 197 clinical geriatric participants with a comorbid anxiety and unipolar mood disorder, and a non-clinical control sample ( N = 59). Results: The internal consistency and convergent validity with other measures of anxiety was adequate for GAI and GAI-SF. Divergent validity from depressive symptoms was good in the clinical sample but weak in the total and non-clinical samples. Divergent validity from cognitive functioning was good in all samples. The one-factor structure was replicated for both measures. Receiver Operating Characteristic analyses indicated that the GAI is more accurate at identifying clinical status than the GAI-SF, although the sensitivity and specificity for the recommended cutoffs was adequate for both measures. Conclusions: Both GAI and GAI-SF show good psychometric properties for identifying geriatric anxiety. The GAI-SF may be a useful alternative screening measure for identifying anxiety in older adults.